Earlier Outbreak Detection—A Generic Model and Novel Methodology to Guide Earlier Detection Supported by Data From Low- and Mid-Income Countries - Steele, Lindsay; Orefuwa, Emma; Bino, Silvia; Singer, Shepherd Roee; Lutwama, Julius; Dickmann, Petra (Frontiers in Public Health, 2020)
Infectious disease outbreaks can have significant impact on individual health, national economies and social wellbeing. Through early detection of an infectious disease, the outbreak can be contained at the local level, thereby reducing adverse effects on populations. Significant time and funding have been invested to improve disease detection timeliness. However, current evaluation methods do not provide evidence based suggestions or measurements on how to detect outbreaks earlier. Key conditions for earlier detection and their influencing factors remain unclear and unmeasured. Without clarity about conditions and influencing factors, attempts to improve disease detection remain ad-hoc and unsystematic. Methods: We developed a generic five-step disease detection model and a novel methodology to use for data collection, analysis and interpretation. Data was collected in two workshops in Southeast Europe (n=33 participants) and Southern and East Africa (n=19 participants) representing mid- and low-income countries. Through systematic, qualitative and quantitative data analyses, we identified key conditions for earlier detection and prioritised factors that influence them. As participants joined a workshop format and not a experimental setting, no ethics approval was required. Findings: Our analyses suggest that governance is the most important condition for earlier detection in both regions. Facilitating factors for earlier detection are risk communication activities such as information sharing, communication and collaboration activities. Impeding factors are lack of communication, coordination and leadership. Interpretation: Governance and risk communication are key influencers for earlier detection in both regions. However, inadequate technical capacity, commonly assumed to be a leading factor impeding early outbreak detection, was not found a leading factor. This insight may be used to pinpoint further improvement strategies.